Status Quo on Graphene Electrode Catalysts for Improved Oxygen Reduction and Evolution Reactions in Li-Air Batteries - Ganesh Gollavelli; Gangaraju Gedda; Raja Mohan; Yong-Chien Ling (Molecules, 2022)
Reduced global warming is the goal of carbon neutrality. Therefore, batteries are considered to be the best alternatives to current fossil fuels and an icon of the emerging energy industry. Voltaic cells are one of the power sources more frequently employed than photovoltaic cells in vehicles, consumer electronics, energy storage systems, and medical equipment. The most adaptable voltaic cells are lithium-ion batteries, which have the potential to meet the eagerly anticipated demands of the power sector. Working to increase their power generating and storage capability is therefore a challenging area of scientific focus. Apart from typical Li-ion batteries, Li-Air (Li-O2) batteries are expected to produce high theoretical power densities (3505 W h kg−1), which are ten times greater than that of Li-ion batteries (387 W h kg−1). On the other hand, there are many challenges to reaching their maximum power capacity. Due to the oxygen reduction reaction (ORR) and oxygen evolution reaction (OES), the cathode usually faces many problems. Designing robust structured catalytic electrode materials and optimizing the electrolytes to improve their ability is highly challenging. Graphene is a 2D material with a stable hexagonal carbon network with high surface area, electrical, thermal conductivity, and flexibility with excellent chemical stability that could be a robust electrode material for Li-O2 batteries. In this review, we covered graphene-based Li-O2 batteries along with their existing problems and updated advantages, with conclusions and future perspectives.